2001
DOI: 10.1002/app.1250
|View full text |Cite
|
Sign up to set email alerts
|

Studies on high‐speed melt spinning of noncircular cross‐ section fibers. I. Structural analysis of as‐spun fibers

Abstract: Flat fibers and hollow fibers were prepared through the high-speed melt spinning of poly(ethylene terephthalate) (PET), and the structures of these fibers were compared with those of circular fibers. The cross-sectional shape of each fiber changed to a dull shape in comparison with that of the respective spinning nozzle. The change in the cross-sectional shape was slightly suppressed with an increase in the take-up velocity. There was a significant development of structural variation in the cross section of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 8 publications
1
41
0
Order By: Relevance
“…In the past, surface tension was observed as a major factor responsible for the fi lament cross-sectional shape (Ziabicki, 1967;Takarada et al ., 2001;Rawal and Davies, 2005;Rawal and Davies, 2006). However, an increase in the cooling rate along with a higher viscosity of the melt can signifi cantly reduce the deviation of the fi lament shapes from their corresponding slot geometries.…”
Section: Modeling Of Polymer Fl Ow Inside the Spinneretmentioning
confidence: 97%
“…In the past, surface tension was observed as a major factor responsible for the fi lament cross-sectional shape (Ziabicki, 1967;Takarada et al ., 2001;Rawal and Davies, 2005;Rawal and Davies, 2006). However, an increase in the cooling rate along with a higher viscosity of the melt can signifi cantly reduce the deviation of the fi lament shapes from their corresponding slot geometries.…”
Section: Modeling Of Polymer Fl Ow Inside the Spinneretmentioning
confidence: 97%
“…Polymer Processing XXVI (2011) Karaca and Ozcelik (2007) that change in cross-sectional shape from circular to triangular configuration had only small effect on crystallinity of the hollow fibers. Takarada et al (2001a) also mentioned for their study on high speed melt spinning that change in cross-sectional shape did not have much effect on structural development in fibers. We further investigated orientation distribution in fibers, and results in plots of averaged diffraction intensity with tilt angles for circular vs. triangular hollow PP25 fibers spun at 260 8C, W 0.32 g/min/ hole, V 900 m/min were shown in Fig.…”
Section: Effect Of Take-up Velocitymentioning
confidence: 95%
“…Study on melt spinning of circular hollow polypropylene fibers at low take up speed range revealed that spinning temperature was the most critical factor affecting percent hole area in fibers, followed by polymer throughput rate (Oh et al, 1998). Takarada et al (2001a) studied structural development of flat fibers and circular hollow fibers in spin-line. They commented that, unlike flat fibers, structural development of hollow fibers was found difficult to predict because effect of air inside fibers was ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990s, methods to produce high-molecular-weight PET fibers were researched (Ito et al, 1990;Huang et al, 1994). In recent years, a number of methods have been investigated to produce highstrength fibers by controlling the melt structure during the melt spinning process (Kikutani et al, 1996;Radhakrishnan et al, 1997;Jeon et al, 1998;Takarada et al, 2001;Masuda et al, 2004;Nakata et al, 2004;Masuda et al, 2010). Among these methods, the conjugated melt spinning process is used in the present study (Radhakrishnan et al, 1997;Nakata et al, 2004).…”
Section: Introductionmentioning
confidence: 98%